Aerial mapping of Kuala Kangsar, Perak - Ibrahim, Illyani; Abdullah, Alias; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana (2020)
Drone aerial image of Kuala Kangsar Royal Town